Peradaban Islam Dinasti Mamluk Mesir : Dampak dan Pengaruh Perang Utsmaniyyah-Mamluk terhadap Dunia Islam - Hamdan Nayl Erriziq; Sinta Setiawati; Padilah S. Kholik; Ahmad Maftuh Sujana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the significant role of the Mamluk Dynasty of Egypt in the history of Islamic civilization during the medieval period and examines the impact of its conflict with the Ottoman Empire. The Mamluk Dynasty, ruling from 1250 to 1517 CE, was uniquely established by former military slaves who rose to power. The dynasty played a crucial role in defending the Islamic world from Mongol invasions and Crusader attacks, notably through its victory at the Battle of 'Ain Jalut. However, in its final decades, the Mamluks suffered from internal strife, corruption, and failure to adapt to modern military developments. This study employs a descriptive qualitative and historical research approach, utilizing both primary and secondary sources. The main focus is the political and military confrontation between the Mamluks and the Ottomans, culminating in two decisive battles Marj Dabiq (1516 CE) and Ar-Raidaniyah (1517 CE) which ended Mamluk rule and marked the beginning of Islamic political unification under the Ottoman Caliphate.